THE INFORMATION TECHNOLOGY TRAINING FOR EDUCATORS IN ORDER TO IMPROVE THE QUALITY OF LEARNING IN BOARDING SCHOOL NURUL ANSOR KARAWANG - Sri Handayani (IKIP Siliwangi Bandung, 2020)
The background of this study is the existence of problems in the conventional learning process in boarding schools that led to declining interest in learning so that students affect on the number of students decreasing each year. The purpose of this research is 1). To determine how the Information Technology Training for Educators to Improve the Quality of Learning Pondok Pesantren Nurul Ansor Karawang, 2). To determine the impact of Information Technology training to students learning interest. The theory used in this research is the training concept, the concept of learning and the concept of a boarding school. The method used qualitative descriptive approach and qualitative methods. This study uses interview and observation techniques.Two educators and five students’ representatives. Research in Pondok Pesantren Nurul Ansor is a learning process that conventionally can be converted into innovative learning and varied with the training information technology for educators so that the learning process more quality and learning interest of students increased sharply so as to produce graduate students are more qualified and capable competitive with the outside world.